Synthesis and Antibacterial Testing of Cu(II)-3-Picolylamine Complexes - Ninna Arifatun Nurul Azizah; Monica Hening Citra Dewi; Sentot Budi Rahardjo; Soerya Dewi Marliyana (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
The synthesis and characterization of a novel Cu(II)-3-picolylamine complex were successfully carried out, aiming to explore the structural properties and antibacterial potential. The complex was synthesized by reacting CuSO4.5H2O with 3-picolylamine in a 1:4 molar ratio, yielding a dark blue precipitate (78.14% yield). Characterization techniques, including UV-Vis spectroscopy, FTIR, thermal analysis (TG/DTA), magnetic susceptibility, and powder XRD, confirmed the formation of the complex with the proposed formula [Cu(3-picolylamine)4]SO4.5H2O. The complex exhibited a square planar geometry around the Cu(II) ion, coordinated through nitrogen donor atoms of the ligand, with the sulphate ion acting as a counter ion. Thermal analysis revealed a two-stage decomposition process, with the release of five water molecules at 55–130°C and ligand decomposition at higher temperatures. Magnetic susceptibility measurements indicated paramagnetic behaviour with an effective magnetic moment of 1.86 BM, consistent with a d9 configuration. Despite its well-defined structure, the complex showed no antibacterial activity against Staphylococcus epidermidis ATCC 12228 and Pseudomonas aeruginosa ATCC 27853 at all concentrations up to 1000 ppm. The lack of activity was attributed to reduced lipophilicity and the presence of hydrophilic counterions, hindering bacterial cell wall penetration.